Border And Territorial Problems of Uzbekistan at The Current Stage - Toshqobilov Umid Sharofiddinovich; Shaydullayev Dilshodbek Anvarovich; Xushboqov Ashurali Abdullayevich (Zien Journals, 2021)
This article provides a scientific analysis of the policy of the Republic of Uzbekistan on delimitation and demarcation of borders with neighboring Central Asian countries during the years of independence, mechanisms for resolving territorial and border issues, agreements between states, enclaves and their status. The policy of the Republic to improve the conditions at border checkpoints with neighboring countrieshas also been considered through a comparative analysis of the literature.
Keywords: Central Asia; territory; delimitation; demarcation